Mustajab / Anis Athierah Bahari - Bahari, Anis Athierah (2020)
Mustajab is a heat lotion under by a company called Dunia Herbs.There is 4 different type of Mustajab lotion. Each lotion has different names. purposes and heat. Main ingredients in Mustajab is ginger extract and key lime. Product : the yellow is called Mustajab Pati halia, Green is Mustajab Pati Halia Limau Nipis, Orange is Mustajab Pati Halia Extra Hot and the Red is Mustajab Pati Halia Super Hot.This lotion free from having muscle aches pain, bloated and many more.The heat lotion contain level from 1 to 60